Novel 1, 4‐Substituted‐1, 2, 3‐Triazoles as Antitubercular Agents. Issue 5 (18th March 2015) - Altimari, Jarrad M.; Hockey, Samantha C.; Boshoff, Helena I.; Sajid, Andaleeb; Henderson, Luke C.
Abstract Tuberculosis (TB) remains a pressing unmet medical need, particularly with the emergence of multidrug‐resistant and extensively drug‐resistant tuberculosis. Here, a series of 1, 4‐substituted‐1, 2, 3‐triazoles have been synthesized and evaluated as potential antitubercular agents. These compounds were assembled via click chemistry in high crude purity and in moderate to high yield. Of the compounds tested, 12 compounds showed promising antitubercular activity with six possessing minimum inhibitory concentration (MIC) values <10 μg mL−1, and total selectivity for Mycobacterium tuberculosis (Mtb) growth inhibition. A second set of 21 compounds bearing variations on ring C were synthesized and evaluated. This second library gave an additional six compounds displaying MIC values ≤10 μg mL−1 and total selectivity for Mtb growth inhibition. These compounds serve as an excellent starting point for further development of antitubercular therapies.